2014
DOI: 10.1002/eji.201444522
|View full text |Cite
|
Sign up to set email alerts
|

Human fibrocytic myeloid‐derived suppressor cells express IDO and promote tolerance via Treg‐cell expansion

Abstract: By restraining T-cell activation and promoting Treg-cell expansion, myeloid-derived suppressor cells (MDSCs) and tolerogenic DCs can control self-reactive and antigraft effector T cells in autoimmunity and transplantation.Their therapeutic use and characterization, however, is limited by their scarce availability in the peripheral blood of tumor-free donors. In the present study, we describe and characterize a novel population of human myeloid suppressor cells, named fibrocytic MDSC, which are differentiated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 45 publications
1
87
0
2
Order By: Relevance
“…In fact, some studies have shown that fibrocytes represent a unique subset of MDSCs that differentiate from M-MDSCs in the presence of IL-4. These cells can suppress immune responses through expression of indoleamine oxidase (IDO) and expansion of Tregs (86,87).…”
Section: Mdscs As Biomarker Of Tumor Progression and Responsiveness Tmentioning
confidence: 99%
“…In fact, some studies have shown that fibrocytes represent a unique subset of MDSCs that differentiate from M-MDSCs in the presence of IL-4. These cells can suppress immune responses through expression of indoleamine oxidase (IDO) and expansion of Tregs (86,87).…”
Section: Mdscs As Biomarker Of Tumor Progression and Responsiveness Tmentioning
confidence: 99%
“…Recent studies suggest that Gr1 + myeloid-derived monocytic cells and MDSCs can transdifferentiate into extracellular matrix (collagen type I)-producing fibrocytes, a mechanism involving CD4 + T-cells, IL-2, IL-4, IFN-γ and TNF, GM-CSF/G-CSF, Kruppel-like factor 4 and fibroblast-specific protein 1 [68][69][70]. Fibrocytic MDSCs were found to interact with activated T-cells in a cell contact dependent manner, resulting in the production of IDO and leading to Treg expansion [69].…”
Section: Mdsc Plasticity/fibrocytic Mdscsmentioning
confidence: 99%
“…Fibrocytic MDSCs were found to interact with activated T-cells in a cell contact dependent manner, resulting in the production of IDO and leading to Treg expansion [69]. Fibrocytes can migrate into the tumour stroma microenvironment and further differentiate into myofibroblasts and promote tumorigenesis [71,72] as well as metastasis [73].…”
Section: Mdsc Plasticity/fibrocytic Mdscsmentioning
confidence: 99%
“…Here, one would predict that increased IDO expression is beneficial to the host because it suppresses a key pathogenic cell type in autoimmunity: the antigen-specific effector T cell (35). Moreover, a beneficial effect has been shown after administration of a subset of myeloid cells that increase IDO synthesis, leading to expansion of regulatory T cells and correction of hyperglycemia in a mouse model of type 1 diabetes (36). Similarly, NOD-H2 h4 mice developed an attenuated form of thyroiditis when injected with an adenovirus expressing IDO directly into the thyroid gland one day before and four weeks after the beginning of iodine supplementation in the drinking water (37).…”
Section: Discussionmentioning
confidence: 99%